(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article provides an understanding of mythology, mythology and the meaning and importance of the Holy Qur’an. Mythology and mythology are scientific directions that study how people talk about the world and its peculiarities. This direction is a collection of scientific theories and studies based on historical, religious and national myths. The Holy Qur’an gives advice and wisdom about people’s way of life, worship, relationships between people, the life of this world and the hereafter. The importance of these topics and their place in the history of mankind is emphasized.